Implementation of NPIVL to Improve Critical Thinking Skills of Pre-Service Physics Teacher - Sri Hartini; Liliasari Liliasari; Parlindungan Sinaga; Ade Gaffar Abdullah (Universitas Lambung Mangkurat, 2022)
This study aimed to describe the critical thinking skills of pre-service physics teacher through the implementation of the Nuclear Physics Inquiry Virtual Laboratory (NPIVL) program. This study used a quantitative pre-experimental study with one group pretest-posttest design involving 14 pre-service physics teachers at one of universities in Banjarmasin, South Kalimantan. The research sample was taken using purposive sampling. The instrument used in this study was a test of critical thinking skills with 25 essay type questions. The questions were compiled based on five indicators of critical thinking skills, namely elementary clarification, basic support, inference, advanced clarification, and strategy and tactics. Data were analyzed using quantitative descriptive. Based on the results of the study, it was found that pre-service physics teachers’ critical thinking skills had a normalized N-gain of 0.33 in the medium category. The percentage of the increase in critical thinking skills indicators was varied, from the largest were basic support, elementary clarification, inference, advanced clarification, and the smallest was strategy and tactics. Based on these findings it can be concluded that the implementation of the NPIVL program can improve the thinking skills of pre-servive physics teacher.